Fractalkine Signaling Attenuates Perivascular Clustering of Microglia and Fibrinogen Leakage during Systemic Inflammation in Mouse Models of Diabetic Retinopathy - Mendiola, Andrew S.; Garza, Rolando; Cardona, Sandra M.; Mythen, Shannon A.; Lira, Sergio A.; Akassoglou, Katerina; Cardona, Astrid E. (Frontiers in Cellular Neuroscience, 2017)
Fractalkine (FKN) is a chemokine expressed constitutively by healthy neurons and signals to microglia upon interaction with the FKN receptor, CX3CR1. Signaling between FKN and CX3CR1 transduces inhibitory signals that ameliorate microglial activation and proinflammatory cytokine release in neuroinflammatory conditions. The aim of this study is to determine the mechanisms associated with microglial activation and vascular leakage during diabetic retinopathy and under conditions of low-level endotoxemia, common in diabetic patients. Utilizing the Ins2Akita strain (Akita), a mouse model of type 1 diabetes, our results show that leakage of the blood-protein fibrin(ogen) into the retina occurs as a result of chronic (4 months) but not acute (1.5 months) hyperglycemia. Conversely, inducing endotoxin-mediated systemic inflammation during acute diabetes resulted in fibrinogen deposition in the retina, a phenotype that was exacerbated in mice lacking CX3CR1 signaling. Systemic inflammation in Cx3cr1–/– mice led to robust perivascular clustering of proliferating microglia in areas of fibrinogen extravasation, and induced IL-1b expression in microglia and astrocytes. Lastly, we determined a protective effect of modulating FKN/CX3CR1 signaling in the diabetic retina. We show that intravitreal administration of recombinant FKN into diabetic FKN-KO mice, reduced fibrinogen deposition and perivascular clustering of microglia in the retina during systemic inflammation. These data suggest that dysregulated microglial activation via loss of FKN/CX3CR1 signaling disrupts the vascular integrity in retina during systemic inflammation.